PERSEPSI MASYARAKAT TERHADAP PERANAN KEPALA DESA DAN BADAN PERMUSYAWARATAN DESA LUBUK BILANG KECAMATAN RAMBAH SAMO KABUPATEN ROKAN HULU - Zikri, Zikri; Erlinda, Sri; Zahirman, Zahirman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study was motivated by the bottom of the village say that remainsthe same from the village in September 2007, such as roads, information, education andconstruction of sports facilities. The problem of this research is How the PublicPerceptions of the Role of the Village Head and Village Consultative Body LubukBilang Kec.Rambah Kab.Rokan Hulu Samo ?, and this study aims to determine the roleof the Public Perception of head Village and Village Consultative Body Lubuk BilangKec.Rambah Samo Kab.Rokan Hulu. The population in this study is the village of LubukBilang community numbering 1622 people. This research using the technique ofpurposive sampling, the sampling technique based on certain considerations, such asthe person deemed most out of what is expected to facilitate the researchers to exploreobjects / situations studied, the authors took a sample of Ninik Mamak 7, ProminentYouth 15 and Women's Representation 15 people, who then called the respondent. Datawere collected through questionnaires, interviews, observation and documentation. Inanalyzing the data using quantitative descriptive analysis.Respondents based on indicators such as the village chief task quite well with thepercentage (57.43), Authority Village Head (56.31%), and the obligation of the VillageHead (49.58%). While respondents to the function of BPD Less Good (32.43%),andliabilities BPD Good Enough by percentage (50.68) The results of the study to thevillage chief of all respondents who answered "Good" with a percentage of 55.98%.Then for the Village Consultative Body of the total respondents who answered "Good"with a percentage of 48.2%.With can be concluded that the public perception of the role of the village Head andVillage Consultative Body Lubuk Tell Kec.Rambah Samo Kab. Rokan Hulu is PrettyGood, can be seen by a benchmark in the results is the number who answered "Good"as much as 55.98% for the village chief and 48.2% for BPD are in the range of 33.34%-66.66%.Keywords: The village head, village consultative body.